PELAYANAN PUBLIK SEBAGAI INSTRUMEN PERWUJUDAN GOOD GOVERNANCE MELALUI PELAYANAN ADMINISTRASI KEPENDUDUKAN - Sugiarto, Refania Varetta; Murofikoh, Dede Ika; Sandi, Mochamad (SINERGI : Jurnal Riset Ilmiah, 2024)
Higher Education Dharma. When the function of both instructors and students is integral to the nature of the activity. It is believed that via participating in PKM (Community Service activities), professors, students, and members of the community will work together in harmony to raise awareness of the community's unique needs. The goal of the government, as well as regional, sub-district, and village administrations, is to ensure that all citizens are treated fairly when applying for and receiving population documentation via the implementation of the Population Administration Services system. Observation, interviews, and documentation are the main tools for gathering information in this qualitative descriptive research method. Population administration services grounded on good governance principles are essential to enhancing the quality of public services. This is driven by the need for public service providers in population administration services that exhibit excellent governance, as well as the societal aspirations for quality public services during this decentralization age.